Connecting the potential theory to the quantum field theory - Sazdjian, H. (Condensed Matter Physics, 1998)
A constraint theory is applied to two-particle systems to construct Poincare´ invariant wave equations with interaction potentials. The latter can be determined in the quantum field theory from Feynman diagrams. Their properties are analyzed in the case of QED. The constraint theory provides a consistent means for solving the Bethe–Salpeter equation with covariant propagators.